Evaluasi Penerapan Optimasi Pendapatan Melalui Pajak Reklame dalam Meningkatkan Pendapatan Asli Daerah Kota Kendari Tahun 2018-2022 - Lutfian, Wa Ode; Nurmantu, Safri (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
This study aims to determine and evaluate the application of revenue optimization through billboard tax in increasing Kendari City Local Revenue, inhibiting and supporting factors and efforts to overcome inhibiting factors in the application of revenue optimization through billboard tax in increasing Kendari City Local Revenue. The research approach used is descriptive qualitative with data collection techniques through in-depth interviews (In-depth Interview) The informants were determined using a purposive sampling technique, involving three people from the Kendari City Regional Revenue Agency as key informants, one person from academia, and one person from the taxpayer. The research instrument used was the researcher himself, with data collected through field observations, interviews, and documentation. The results showed that revenue optimization through billboard tax aims to increase local revenue through more efficient and effective tax management and collection by increasing taxpayer compliance and utilization of billboard tax which has not been optimal and is expected to increase significantly to support development and improve public services.